Immersive visualizations in a VR cave environment for the training and enhancement of social skills for children with autism - Matsentidou, Skevi; Poullis, Charalambos (My University, 2014)
Autism is a complex developmental disorder characterized by severe impairment in social, communicative, cognitive and behavioral functioning. Several studies investigated the use of technology and Virtual Reality for social skills training for people with autism with promising and encouraging results (D. Strickland, 1997; Parsons S. & Cobb S., 2011). In addition, it has been demonstrated that Virtual Reality technologies can be used effectively by some people with autism, and that it had helped or could help them in the real world; (S. Parsons, A. Leonard, P. Mitchell, 2006; S. Parsons, P. Mitchell, 2002). The goal of this research is to design and develop an immersive visualization application in a VR CAVE environment for educating children with autism. The main goal of the project is to help children with autism learn and enhance their social skills and behaviours. Specifically, we will investigate whether a VR CAVE environment can be used in an effective way by children with mild autism, and whether children can benefit from that and apply the knowledge in their real life.
Keywords: Autism; Immersion; Training; Visualization; VR systems and toolkits